Optimization for starve fed single screw extrusion of polymeric materials – simulations - Nastaj, Andrzej (Polimery, 2020)
Optimization method for starve fed single screw extrusion has been developed based on the computer model of the process and using evolutionary techniques. The method is based on the starve fed single screw extrusion simulation program GSEM and especially developed to this aim optimization program GASEO. Program GSEM is the source of optimization data, and program GASEO is the optimization tool. Simulation studies have been performed on the starve fed single screw extrusion, and optimization of the selected process parameters, screw rotational speed and screw metering section length has been carried out from the point of view maximum extrusion throughput and minimum power consumption. The results of simulation optimization have been compared with the experimental optimization, indicating the advantages of simulation studies. It has been concluded that optimization based on experimental research is ineffective and the optimization of extrusion based on simulation tests using evolutionary techniques can be a suitable alternative in this regard.